Nhìn lại một thập niên nghiên cứu áp dụng ngôn ngữ học tri nhận vào giảng dạy ngoại ngữ.. /Phạm Thị Hồng Nhung. - Phạm, Thị Hồng Nhung.
Since its birth in the 70s, cognitive linguistics has greatly contributed to a comprehensive understanding of the connection between language and mind, of how language is learnt, especially of how human beings extract language knowledge from language use. Research on the application of cognitive linguistics to foreign language teaching for the last 10 years has provided valuable implications for language teachers.